Systems dynamics and the spatial distribution of methane emissions from African domestic ruminants to 2030 - Herrero, Mario; Thornton, Philip K.; Kruska, Russell L.; Reid, Robin S. (Elsevier, 2008)
Livestock production systems in Africa are experiencing rapid changes in structure and function due to increased demands for livestock products from a more prosperous and ever-increasing human population. Some of these changes could lead to increased emissions of greenhouse gases. This paper explores the magnitudes of changes in production systems as a function of increased population densities and climate change. This paper also quantifies the methane emissions from African cattle, goats and sheep from 2000 to 2030. The study integrates methodologies from different disciplines to derive spatially explicit distributions of methane emissions from domestic ruminants and their changes as livestock production systems evolve. A livestock systems classification framework was used to differentiate pastoral and crop– livestock systems using agro-ecological thresholds based on temperature and length of growing period (hyper-arid, arid, humid and temperate regions), the extent of irrigation and human population densities. Livestock numbers (tropical livestock units, TLU) were estimated from FAO data for each country and production system defined. Projections of livestock populations were derived from analysis of demand shifts in livestock products, and livestock systems changes estimated on the basis of potential climate change and population density change to 2030. For the estimation of diets for ruminants, Africa was split into regions (East, West, Southern, Central and North Africa, and The Horn of Africa) and diets for both the rainy and the dry seasons were estimated from literature reviews for each livestock species in each production system in each region. Feed intake, livestock production and the computation of methane emissions were obtained using a previously validated and widely used mechanistic model of digestion and metabolism in ruminants. Results suggest that (1) Africa produced around 7.8 million tonnes of methane/year in 2000. This figure is likely to increase to 11.1 million tonnes/year by 2030. (2) Methane emissions per tropical livestock unit (TLU, 250 kg bodyweight) can vary from 21 to 40 kg/(TLU year), depending on the production system and the region. (3) The highest emissions per animal come, and will continue to come, from ruminants in mixed crop–livestock systems. (4) The regions producing the highest concentrations of methane, now and in the future, are in general terms, The Horn of Africa, West and East Africa. (5)The average emission factors obtained in this study (31.1 kg/(methane (TLU year))) are in close agreement with the emission factors used by the International Panel on Climate Change (IPCC) for African ruminants (32 kg methane per animal per year). (6) The methodology employed in this study permits the disaggregation of methane emissions by country and production system, thus allows us to quantify changes in emissions as climate changes and production systems evolve. The results of the study are compared with those obtained in other studies around the world and its implications are discussed in relation to how systems are likely to evolve in Africa.